PEMOTIVASIAN GURU DAN SUPERVISI KEPALA SEKOLAH SEBAGAI UPAYA MENINGKATKAN KINERJA GURU DI SMK NEGERI RAJAPOLAH - SRI NURHAYATI (KULTURA DIGITAL MEDIA ( Research and Academic Publication Consulting ), 2021)
Evidence that the performance of teachers at SMK Negeri Rajapolah is not yet professional, in carrying out their main duties and functions, is teaching planning that is not in accordance with the demands, teaching that is not in accordance with planning, evaluating student learning outcomes with the right technique and it is proven that the students have not been able to learn properly. good or meaningful. Teacher performance has not been optimal, especially in terms of discipline and compliance with regulations. The research formula is